UPAYA UNTUK PENINGKATAN EFISIENSI PEMANFAATAN GURU SDN BERDASARKAN LOKASI DI KECAMATAN PADANG BARAT KOTA PADANG - 103-111 . Yuda Satriadinata (Universitas Negeri Padang, 2013)
This study aims tofind solutions tothe teachershortagein the district ofWest PadangPNS.The research questionin this finalassignment such howmany State Elementary School (SES)which may be incorporatedin the Districtof WestPadang, whathappensto theteacherefficienciesif we do the mergerof state elementary. The types of dataused inthis finalassignment areprimary data andsecondary data.Primary dataarethe coordinates of theSESwhilesecondary dataisthe numberof teachers, number of students, numbers of student’s group, the name andaddress ofthe school.Data collection methodswill be usedin this final assignment isthefield surveymethods. The survey that will be done islocation coordinatesofState Elementary School by using GPS. The results ofthis studyit appears there wassomedecentSESto be mergedin theWesternDistrictof Padangthatthe25 SESand 28SES Purusinto oneschool.01 SESand19SES Belakang tangsiinto oneschool.03SES, 04SES,13 SESand21SES Purusinto threeschools.07SES,11SES and17SES belakang tangsiinto twoschools.With the merger of a fewSES, the class teacher efficiency as 6 people or 15.38% of the 39 teachers are needed, the religious teacher 2 people or 25% of the required 8 teacher, gym teacher 2 people or 28.57% of the 7 teachers needed. And 4 head master excess. Key words : Efficiency, SES Teacher, and Location